Pregnenolone derivatives as potential anti‐lung cancer agents: A combined in silico and in vitro approach. Issue 6 (6th May 2022) - Sethi, Arun; Yadav, Priyanka; Singh, Ranvijay Pratap; Kumar, Saurabh; Parveen, Shama; Singh, Asmita; Yadav, Astha; Banerjee, Monisha
Abstract: Synthesis of C‐3 and C‐20 pregnenolone derivatives using Steglich and Heck reaction has been reported. The structures of compounds were established by 1H, 13C NMR, NOESY, FT‐IR, and ESI‐MS. The anticancer activity against lung cancer proficiency assessment was performed using the prediction of activity spectra for substances (PASS) technique and the results were compared with the FDA‐approved lung cancer drug dacomitinib. Molecular docking studies were carried out to investigate the inhibitory action of steroidal derivatives against the lung cancer cell protein (2ITO). The result of the docking exhibited a significant inhibitory action against the lung cancer protein (2ITO) and the binding energy (ΔG) values of 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 against the protein 2ITO were found to be −10.1, −10.8, −9.2, −9.4, −10.1, −9.4, −11.0, −10.9, −9.7, and −9.5 Kcal/mol, respectively. In vitro lung cancer activity analyses of these compounds against lung cancer cell line (A549) showed that compounds 2 and 3 were more potent than other compounds. Results of in silico and in vitro analysis revealed that they showed good correlation. Drugs likeness and ADMET analysis of all derivatives have also been studied. Abstract : The C‐3 and C‐20 pregnenolone derivatives have been synthesized using Heck and Steglich reactions. Molecular docking studies carried out to investigate the inhibitory action of steroidal derivatives against the lung's cancer cell protein (2ITO) suggest that these synthesized derivatives might be used against the protein 2ITO. In vitro lung's cancer activity analyses of these compounds investigated against lung cancer cell line (A549) revealed that 2 and 3 showed anticancer activity at a lower dose, thus they appear to be better anti‐cancerous drugs.